2008
DOI: 10.1075/eurosla.8.07gab
|View full text |Cite
|
Sign up to set email alerts
|

Interpreting tense in a second language

Abstract: The question of whether adult native speakers of Chinese, a language that does not morphosyntactically represent tense, are able to acquire tense in English has been a topic of great interest in part because it allows us to examine whether there is a critical period for features that are not instantiated in the native language (Hawkins 2001;Hawkins & Liszka 2003;Lardiere 1998aLardiere , 2003. While most previous studies have focused on production data, the present study examines the semantics of tense, investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 42 publications
0
4
1
Order By: Relevance
“…The L1 Japanese and L1 Korean learners performed well as expected. Gabriele and Maekawa's (2008) findings provide evidence against Hawkins and Liszka's (2003) proposal of a permanent syntactic deficit in the L2 when a feature such as [epast] is not instantiated in the L1.…”
Section: Tense and Aspect In L2 Englishcontrasting
confidence: 47%
See 1 more Smart Citation
“…The L1 Japanese and L1 Korean learners performed well as expected. Gabriele and Maekawa's (2008) findings provide evidence against Hawkins and Liszka's (2003) proposal of a permanent syntactic deficit in the L2 when a feature such as [epast] is not instantiated in the L1.…”
Section: Tense and Aspect In L2 Englishcontrasting
confidence: 47%
“…They allowed a perfective reading for the English past progressive even when the L1 Japanese interpretation is progressive, leading Gabriele, Martohardjono, and McClure (2005) to suggest that the perfective is a default interpretation in the mental representation of te-iru. Gabriele and Maekawa (2008) compared three groups of L2 English learners -native speakers of Chinese (n ¼ 32), Korean (n ¼ 18), and Japanese (n ¼ 55) -at di¤erent levels of proficiency. Contrary to Japanese and Korean, Chinese does not encode tense morpho-syntactically and presumably does not have a Tense projection (Lin 2005).…”
Section: Tense and Aspect In L2 Englishmentioning
confidence: 99%
“…12. Results of the English NSs as well as the L2 English intermediate-and highprofi ciency learners for the accomplishments in the present progressive and the simple past were also reported in Gabriele and Maekawa ( 2008) .…”
Section: Discussionmentioning
confidence: 86%
“…Previous research on the acquisition of English temporal morphology, and especially the interpretation of findings by Gabriele and Maekawa (), coupled with the processing results of Chan (), suggest that the deictic principle is also in action when Chinese speakers approach English. However, it works against them to some extent.…”
Section: Discussionmentioning
confidence: 93%
“…For example, Lardière's () fossilized speaker Patty provided the ‐ed marker in around 34% of obligatory contexts, while Yang and Lyster's () instructed learners provided 55–63% past tense marking in oral (pretest) production and 65–73% in written production. Investigating interpretation, Gabriele and Maekawa () offered evidence of successful comprehension of the English temporal contrasts by advanced levels of proficiency. Recently, Chan () showed that in processing English sentences online, advanced learners were not sensitive to omitted past tense morphology (e.g., * Yesterday several large snakes escape‐Ø from their cage at the zoo) but they were sensitive to meaning clashes between adverbial and tense information (e.g., # Tomorrow several large snakes escaped from their cage at the zoo ).…”
Section: Acquisition Of Temporality Markingmentioning
confidence: 99%